Межкультурно-коммуникативное обучение иностранным языкам - Jan Gallo (Studia Rossica Posnaniensia)
This paper discusses the issue of cross-cultural foreign language teaching accentuating Russian Foreign Language Teaching at colleges in Slovakia. In the introduction some ideas on the position and meaning of cross-cultural communication are presented. In the second part there are explanations of the term cross-cultural communication by some linguists and methodists, as well as its implementation on several levels. In the third part attention is focused on the relations between cross-cultural communication and foreign language teaching. The issue of cross-cultural (policultural) didactics is also explained. In the fourth part the problem of cross-cultural teaching methodology is discussed. In the fifth part the focus is on presenting a summary of cross-cultural communication teaching practice in the Department of Russian Studies at Constantine the Philosopher University in Nitra. The paper concludes with a summary of the problems investigated.